STUDENTS’ PERCEPTIONS TOWARDS THE USE OF ENGLISH LANGUAGE ON SOCIAL, ACADEMIC AND PROFESSIONAL CONTEXT - Khamkhong, Yongyut (Academic Journal Phranakhon Rajabhat University, 2021)
English education in Thailand is still developing with its world academic ranking often found at low level. Local academics blamed the nationwide system that is focusing on grammar and tutoring style to help students simply ‘pass’ the exam, not communicative skills as it should be. There is a call for teachers to communicate in English with students inside and outside classroom as much as possible. This research aimed to understand students’ perceptions towards the use of English on social, academic and professional context. A set of questionnaires was tested with 81 third-year Business English students, Phranakhon Rajabhat University. Five teachers and 10 students were interviewed. The findings: students’ perception towards the use of English on social context is at High level (X̄=3.70), while on academic context is also at High level (X̄=3.81). Their perception towards the use of English on professional context is at High level (X̄=3.71). The respondents reflected a certain level of fear on grammatical use when communicating in English on both social and academic context. In order to succeed in upgrading students’ English ability, the three functions - teachers, students and the university, must take their parts more seriously.